Cognitive Impairment in Anti-Phospholipid Syndrome and Anti-Phospholipid Antibody Carriers - Fadi Hassan; Mohammad E. Naffaa; Amir Saab; Chaim Putterman (Brain Sciences, 2022)
Cognitive impairment is frequently reported among anti-phospholipid syndrome (APS) patients as well as anti-phospholipid antibody (aPL) carriers, but it is less studied than other manifestations of this condition. Moreover, the exact prevalence of cognitive impairment in these patients has not been accurately determined, mainly due to inconsistency in the tools used to identify impairment, small sample sizes, and variability in the anti-phospholipid antibodies measured and positivity cutoffs. The notion of a direct pathogenic effect is supported by the observation that the higher the number of aPLs present and the higher the load of the specific antibody, the greater the risk of cognitive impairment. There is some evidence to suggest that besides the thrombotic process, inflammation-related pathways play a role in the pathogenesis of cognitive impairment in APS. The cornerstone treatments of APS are anti-coagulant and anti-thrombotic medications. These treatments have shown some favorable effects in reversing cognitive impairment, but solid evidence for the efficacy and safety of these treatments in the context of cognitive impairment is still lacking. In this article, we review the current knowledge regarding the epidemiology, pathophysiology, clinical associations, and treatment of cognitive impairment associated with APS and aPL positivity.